2007
DOI: 10.1093/ndt/gfm264
|View full text |Cite
|
Sign up to set email alerts
|

A prospective national study of acute renal failure treated with RRT: incidence, aetiology and outcomes

Abstract: This is the first national study to describe ARF treated with RRT in all hospital locations. The hypothesis that ARF occurs more frequently than previously thought has been confirmed. This study provides data upon which to base effective decision making for prevention, patient care and resource planning for patients with ARF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
73
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 17 publications
14
73
1
1
Order By: Relevance
“…Among hospitalized Medicare beneficiaries, patients with CKD have a 10-fold higher incidence of AKI. It is unclear whether patients with AKI and prior CKD experience a different disease course and outcomes than those without prior CKD, because data from several studies are conflicting (5)(6)(7). Most studies have suggested that patients with prior CKD are more likely to remain dialysis dependent after an episode of dialysis-requiring AKI (5,8,9).…”
mentioning
confidence: 99%
“…Among hospitalized Medicare beneficiaries, patients with CKD have a 10-fold higher incidence of AKI. It is unclear whether patients with AKI and prior CKD experience a different disease course and outcomes than those without prior CKD, because data from several studies are conflicting (5)(6)(7). Most studies have suggested that patients with prior CKD are more likely to remain dialysis dependent after an episode of dialysis-requiring AKI (5,8,9).…”
mentioning
confidence: 99%
“…15 In a similar study of UK patients, Prescott reported similar findings with respect to an apparent mortality benefit conferred by CKD in AKI. 11 This association of improved mortality was also exhibited in critically ill patients. 16 In 618 patients with AKI from the PICARD study, the mortality among patients with CKD was 31% compared to 40% without CKD.…”
Section: Mortality In Aki On Ckdmentioning
confidence: 83%
“…Our patients were recruited from ICU unit, as in Egypt ARF is usually treated in ICU and attributed mostly to sepsis. The latter was reported as the commonest causative factor of ARF (up to 50%) [2,10,11]. In fact, ARF is nowadays mostly observed as part of the multi-organ dysfunction syndrome in severe sepsis and septic shock [12].…”
Section: Discussionmentioning
confidence: 99%
“…10/40 [25%] of our patients died in the ICU admission period and this agrees with Prescott et al study as many of his deaths [20% -30%] were very early where ARF was sepsis-induced. They concluded that the presence of sepsis increased the risk of death; both as an etiological factor and poor indicator of prognosis in a startling manner [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation